The figure of the interpreter in educational public services. An analysis about the necessity of this professional profile in the educational public services - Criado González, María Inés (Avances en Supervisión Educativa, 2016)
A large number of immigrant children arrive in Spain with no previous knowledge of Spanish and it can be very difficult for their teachers to relate to them and their families. Unable to overcome linguistic barriers, they are forced to rely on other forms of communication and this can often cause misunderstanding between the school staff and the immigrant family. We put forward, as a hypothesis, that the intervention of professional translators and interpreters is needed for immigrant pupils into the Spanish education system to ensure that the process is carried out in accordance with the professional principles of translation and interpreting in several educational centres of the south of Cadiz via a personal and professional analysis of the teachers. This analysis will be done through a survey which has been carried out in these educational centres of the municipalities in order to reach a conclusion which supports the hypothesis.